Organizational Communication and Teachers’ Teamwork Effectiveness in Supporting Digital-Based Instruction: Evidence from a Public Senior High School - Sugiarti, Eni Sri; Dermawan, Erik; Zebua, Feberkatianis; Laia, Febrianus; Yogi, Fransiska Pemeliana; Saputra, Fredy Mitra Rian; Zulfazzly; Pratiwi, Ika (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study analyzes the influence of organizational communication on the effectiveness of teachers’ teamwork at SMAN 4 Kundur, Karimun Regency, Riau Islands Province. Employing a quantitative approach, the study tests the hypothesis that effective organizational communication is positively and significantly correlated with improvements in teachers’ team effectiveness. Recent post-pandemic developments have required more adaptive and transparent communication patterns within school environments. While existing research gaps often emphasize linear communication processes, this study highlights the complexity of effective communication within the school ecosystem. The research adopts an associative research design with a quantitative approach, aimed at explaining the causal relationship or influence between the independent variable (organizational communication) and the dependent variable (teachers’ team effectiveness) through statistical hypothesis testing. Data were collected through a questionnaire survey administered to 40 teachers and analyzed using simple linear regression. The findings indicate that organizational communication has a positive and significant effect on teachers’ team effectiveness at SMAN 4 Kundur, Karimun Regency. The main results demonstrate that open communication patterns, supported by effective formal and informal communication channels, directly enhance coordination, productivity, and the achievement of shared goals among teacher teams. From a managerial perspective, the findings suggest that school principals should optimize internal communication channels to strengthen collaborative team performance, particularly through the provision of interpersonal communication training for teachers.